Evidence of Bos javanicus x Bos indicus hybridization and major QTLs for birth weight in Indonesian Peranakan Ongole cattle - Hartati, Hartati; Utsunomiya, Yuri Tani [UNESP]; Sonstegard, Tad Stewart; Garcia, José Fernando [UNESP]; Jakaria, Jakaria; Muladno, Muladno (Biomed Central Ltd, 2015)
Background: Peranakan Ongole (PO) is a major Indonesian Bos indicus breed that derives from animals imported from India in the late 19(th) century. Early imports were followed by hybridization with the Bos javanicus subspecies of cattle. Here, we used genomic data to partition the ancestry components of PO cattle and map loci implicated in birth weight.Results: We found that B. javanicus contributes about 6-7 % to the average breed composition of PO cattle. Only two nearly fixed B. javanicus haplotypes were identified, suggesting that most of the B. javanicus variants are segregating under drift or by the action of balancing selection. The zebu component of the PO genome was estimated to derive from at least two distinct ancestral pools. Additionally, well-known loci underlying body size in other beef cattle breeds, such as the PLAG1 region on chromosome 14, were found to also affect birth weight in PO cattle.Conclusions: This study is the first attempt to characterize PO at the genome level, and contributes evidence of successful, stabilized B. indicus x B. javanicus hybridization. Additionally, previously described loci implicated in body size in worldwide beef cattle breeds also affect birth weight in PO cattle.
Keywords: Peranakan Ongole; Nellore; Bos indicus; Bos javanicus; Birth weight